Accessibility of University Websites in the Light of WCAG 2.1 Guidelines - Bucko, Jakub; Czarnota, Aleksandra (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
In today’s world, the Internet has become an integral part of academic life, providing access toinformation and educational resources. However, to meet the requirements of equal access, itis essential to ensure that university websites are accessible to everyone, including people withdisabilities.Tis paper focuses on assessing the accessibility of higher education institution websites in relationto the WCAG 2.1 guidelines, with particular attention to the needs of people with visualimpairments. WCAG 2.1 is a standard embedded in the Act on Digital Accessibility of PublicSector Websites and Mobile Applications, outlining the principles of web development that allowindividuals with various disabilities to navigate digital platforms comfortably.Te methodology includes an analysis of website structure, layout, and interface usability, as wellas an evaluation of content readability for visually impaired users. Te study covered 16 publicuniversities in Poland, each located in a diferent voivodeship. Using both automated analysistools and manual evaluation, we identifed areas where university websites can be improved tobetter accommodate the needs of users with visual impairments.Our fndings ofer insights into the current state of digital accessibility in higher education andprovide recommendations for enhancement, aiming to support a more inclusive educational environment.Te presentation will share the research results and foster discussion on future strategiesto improve the accessibility of university websites for visually impaired users, contributing to thedevelopment of a more accessible and equitable academic landscape.